Diesel Oil Biodegradation Process By Mixed Culture Of Hydrocarbon Degrader Bacteria - Mohamad Yani; Yusuf Akbar (Department of Agroindustrial Technology, Bogor Agricultural University, 2009)
Three isolates name as Pseudomonas aeruginosa (PA), Pseudomonas pseudomallei (PP) and Enterobacter agglomerans (EA) are petroleum hydrocarbon degrader bacteria. They were grown in mineral medium and 10% diesel oil as carbon source. The diesel oil biodegradation by PAEA and PPEA are better than single or other mixed cultures. The diesel oil compounds are oxidized to intermediate product and detected as fatty acids ranged of nC18 to nC8, organic acids, and then it was mineralized. The mineralized products measured as methane, carbon dioxide, and carbon monoxide. This result showed that during hydrocarbon biodegradation of aliphatic compounds by those isolates through fatty acids formation, simple organic acids, and simple volatile organic carbon. The mineralized product of methane, carbon dioxide, and carbon monoxide were emitted to the environment. Keywords: Biodegradation, diesel oil, Pseudomonas, Enterobacter, minerallized